2017
DOI: 10.1016/j.conbuildmat.2017.06.064
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the alkali activation conditions of ground granulated SiMn slag

Abstract: The viability of using a SiMn slag as raw material for the preparation of alkali activated binder has been analysed. The slag has been characterized from the physical, chemical, mineralogical and microstructural point of view. The solution used for the alkali activation process was waterglass, which was prepared by the mix of a sodium silicate solution with sodium hydroxide. The influence of the following design parameters in alkali activated pastes has been studied: %Na2O, SiO2/Na2O ratio and activating solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 42 publications
6
29
0
Order By: Relevance
“…The chemical composition of the slag is presented in Table 1. This SiMn slag is an acid slag with moderate hydraulicity [30][31][32] as indicated by its basicity coefficient of 0.73 and its hydraulicity index of 0.85 [27]. The slag mineralogy was identified by X-ray diffractometer (PANalytical, model EMPYREAN) operated at 50 mA and 50 kV, using MoK1 radiation.…”
Section: Experimental 21 Materialsmentioning
confidence: 99%
See 3 more Smart Citations
“…The chemical composition of the slag is presented in Table 1. This SiMn slag is an acid slag with moderate hydraulicity [30][31][32] as indicated by its basicity coefficient of 0.73 and its hydraulicity index of 0.85 [27]. The slag mineralogy was identified by X-ray diffractometer (PANalytical, model EMPYREAN) operated at 50 mA and 50 kV, using MoK1 radiation.…”
Section: Experimental 21 Materialsmentioning
confidence: 99%
“…In present study, the SiMn slag has been used as AAM. The chemical, mineralogical and pozzolanic characteristics of the SiMn waste allow its use as a substrate to obtain alkaline activated materials [27,28]. Previous studies have shown that it is possible to activate the ground SiMn residue with an efficient grinding process, using NaOH and waterglass as activators [27,28].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In relation to that, the geopolymer concretes have experienced a great development [79][80][81]. The geopolymers are generally made by pozzolanic materials containing SiO 2 and Al 2 O 3 activated with alkaline solutions without Portland cement [81][82][83].…”
Section: Present and Future Of Caisson Breakwaters Technology: An Impmentioning
confidence: 99%